Organizational Commitment: Three Research Models Proposal - Aslan, Asst. Prof. Dr. Mustafa (The journal of contemporary issues in business and government, 2021)
Organizational commitment is a vital subject for all organizations that are trying to establish a sustainable business model. In all studies examining the effects of variables on organizational commitment, the research models are designed as all three dimensions of the organizational commitment are distinct variables that are not affecting each other. This research model is valid if the researcher is only trying to investigate the effects of the independent variables on the dimensions. However, if the organizational commitment is being investigated, then the research models should be different. This study tries to examine how the research models should be designed as per research purpose and demonstrates the difference between currently used and the proposed research models by using a sample dataset from a previous study.